Über den lokalen Grenzwertsatz im Falle der stabilen Grenzverteilung - Mitalauskas, A. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Миталаускас. О локальной предельной теореме в случае устойчивого распределения A. Mitalauskas. Lokalinė ribinė teorema stabilaus ribinio pasiskirstymo atveju